Preclinical safety evaluation of biopharmaceuticals: science-based approach of facilitating clinical trials - Cavagnaro, Joy (Henry Stewart Talks, 2009)
Optimization of the clinical development of biopharmaceuticals over the past two decades has relied upon the careful design and judicious use of animals in preclinical studies, This is not only to allow for the early initiation of clinical studies but to support an uninterrupted clinical development program, The approach has been referred to as "case-by-case", an approach which is science-based, question-based, experience-based and targeted based upon product attributes